Development of Web -Based Clinic Management System - ZAMRI, NUR SYAFINAZ; MOHMAD HASSIM, YANA MAZWIN (Applied Information Technology And Computer Science, 2022)
This project is a Clinic Management System proposed to solve the problems encountered in the Medi Ehsan clinic. The problems faced by Medi Ehsan are, this clinic does not have a web-based system. Next, it is difficult for patients to make an appointment with a doctor as they have to go to the clinic counter and line up to make an appointment. Finally, there are problems with the loss of patient data and redundant patient data. This happens when the records stored in the patient file are lost or the patient forgets whether they ever registered or not. Therefore, the objective of this project is to design a web-based clinic management system based on a structured approach. The second objective is to develop a clinic management system using a prototype model. Finally, to test the function of this clinic management system with the user to ensure that it works as planned. This system is developed based on prototype model methodology. Since this is a web-based system, PHP is used as the programming language and xampp as the webserver. This system is intended to assist the clinic organization to handle clinic management. Patients do not have to go to the clinic counter and line up to make an appointment. Patients only need to select the date and doctor available through this system. This can save time and energy. Additionally, patients can change the appointment booking schedule, if there are any unavoidable problems. Furthermore, the system allows administrators and doctors to easily search for specific patient data. Besides, records of these activities are kept in the database. The system can also generate patient reports. Thus, the patient can refer back to the report in the future.